2014
DOI: 10.1080/15438627.2014.915834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Exposure to Mild Simulated Hypoxia on Hormonal Responses to Low-intensity Resistance Exercise in Untrained Men

Abstract: This study examined hormonal responses to low-intensity resistance exercise under mild simulated hypoxia. Ten resistance untrained men performed five sets of 15 repetitions of squat exercise at 30% of 1RM under normobaric hypoxia (FiO2 = 15%) and normoxia in a cross-over and counter-balanced design. Blood lactate (LAC), growth hormone (GH), total testosterone (T) and cortisol (C) were measured at pre-exercise, immediately post-exercise and 15 minutes post-exercise. LAC, GH and T significantly increased immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…While some research has previously demonstrated increased metabolic stress following IHRT (Kon et al, 2010 , 2012 ), conflicting data have been recently reported (Kurobe et al, 2014 ; Ho et al, 2014a ). Kurobe et al ( 2014 ) observed no differences between hypoxic and normoxic training groups performing 3 sets of 10 repetitions of elbow extensions (10RM) with 60 s inter-set rest.…”
Section: Metabolic Stressmentioning
confidence: 97%
See 1 more Smart Citation
“…While some research has previously demonstrated increased metabolic stress following IHRT (Kon et al, 2010 , 2012 ), conflicting data have been recently reported (Kurobe et al, 2014 ; Ho et al, 2014a ). Kurobe et al ( 2014 ) observed no differences between hypoxic and normoxic training groups performing 3 sets of 10 repetitions of elbow extensions (10RM) with 60 s inter-set rest.…”
Section: Metabolic Stressmentioning
confidence: 97%
“…This may account for the findings of no added hypertrophic or strength benefits following IHRT in previous research that has employed inter-set rest periods of 90–120 s (Ho et al, 2014b ; Kon et al, 2014 ). Indeed, Ho et al ( 2014a ) have reported no differences in blood lactate concentrations between hypoxic and normoxic IHRT groups following 5 sets of 15 repetitions of squats (30% 1RM) with 90 s inter-set rest. Therefore, it is likely that inter-set rest periods of 90 s or longer are sufficient to attenuate any hypoxia-mediated rise in metabolic stress, limiting the potential anabolic effects of hypoxia.…”
Section: Metabolic Stressmentioning
confidence: 99%
“…In this case, muscle growth is highly dependent on metabolic factors, and training sets should be conducted to failure [27]. These two points must be considered in both normoxic and hypoxic conditions despite the fact that there is an accelerated build-up of metabolites observed in hypoxia during resistance training with moderate loads [17, 2730], but not with low loads [51]. For instance, similar lactate and anabolic hormone responses were observed for squat exercises (5 sets of 15 repetitions at 30% 1RM, 90 s of rest) in conditions of normoxia, as those for systemic hypoxia (15% of the inspired oxygen fraction [FiO 2 ]) [51].…”
Section: Hypertrophy Trainability In Conditions Of Hypoxiamentioning
confidence: 99%
“…These two points must be considered in both normoxic and hypoxic conditions despite the fact that there is an accelerated build-up of metabolites observed in hypoxia during resistance training with moderate loads [17, 2730], but not with low loads [51]. For instance, similar lactate and anabolic hormone responses were observed for squat exercises (5 sets of 15 repetitions at 30% 1RM, 90 s of rest) in conditions of normoxia, as those for systemic hypoxia (15% of the inspired oxygen fraction [FiO 2 ]) [51]. For this reason, performing a high number of repetitions in each training set is an important detail that could explain the positive results of Manimmanakorn et al [21, 22] given the absence of strength and hypertrophic changes in other studies under similar conditions [14].…”
Section: Hypertrophy Trainability In Conditions Of Hypoxiamentioning
confidence: 99%
“…Data are ranked in order of decreasing oxygen concentration in the inspired gas. Human investigations strongly suggest that the training with 15-13% inhaled oxygen (FiO 2 ) at various time characteristics do not provide any positive changes [15][16][17][18][19][20][21][22][23][24]. 12-10% FiO 2 is the most common concentration caused a positive effect [25-39, 48, 49].…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommementioning
confidence: 99%